PERSONAL AND REGULATORY PREDICTORS OF AGGRESSION - Banshchikova, T.N. (Modern Psychology, 2021)
The article provides data from an empirical study of regulatory and personal predictors of aggression. Conscious self-regulation, life values, sociocultural identity and personal characteristics (Big 5) of the respondents were considered as predictors. It was suggested that the management of aggression is associated with the level of development of the personality-regulatory characteristics of the subject, which have their own socio-cultural conditioning. The study involved 278 teachers from the Stavropol and Krasnodar regions, from the republics of North Ossetia- Alania, Karachay-Cherkessia, Kabardino-Balkaria. By age structure, the sample included teachers from 20 to 72 years old. For diagnostics, we used: questionnaire "Style of self-regulation of behavior", questionnaire of aggression Bass-Darki, methodology "Determination of sociocultural identity", Freiburg multifactorial personality questionnaire, "Morphological test of life values." The results obtained showed that indicators of conscious self-regulation are significant predictors of aggression management. For physical aggression, an important predictor is the regulatory indicator "evaluation of results", and for verbal aggression - "planning". And in the number of personal characteristics, racial tolerance, regional identity and a predisposition to stressful responses to ordinary life situations proceeding in a passive-defensive type make a significant contribution to the management of aggression.
Keywords: conscious self-regulation; aggression; teachers; regulatory and personality predictors